Bai-Hu-Tang regulates endothelin-1 and its signalling pathway in vascular endothelial cells. (10th February 2022) - Feng, Min; Wang, Dongsheng; Wang, Xurong; Yang, Ying; Zhang, Shidong
Abstract: Ethnopharmacological relevance: Bai-Hu-Tang (BHT) is traditionally used to treat human and animal fever syndrome with four symptoms: large and vigorous pulse, large thirst, high sweat, and high heat. Aim of the study: To investigate the mechanism of vasodilation regulation of Bai-Hu-Tang in primary vascular endothelial cells stimulated by lipopolysaccharide (LPS). Materials and methods: A hydrophilic concentrate of BHT was prepared, and the main components of mangiferin and timosaponin BⅡ were determined by HLPC analysis. The rabbit fever model was constructed by intravenous injection of LPS (15 μg/kg body weight), and BHT was gavaged to treat febrile rabbits. After treatment for 6 h, animal peripheral blood was collected, and serum was isolated for endothelin-1 (ET-1) and nitric oxide (NO) assays. Rabbit vascular endothelial cells (RVECs) were isolated and stimulated with 1 μg/mL LPS, and then inflammatory cells were treated with 125 or 250 μg/mL BHT for 24 h. The supernatant cytokines TNF-ɑ, IL-1β, IL-6, and ET-1 were detected by ELISA kits. Gene expression levels of endothelin receptor type B (ETB receptor) were analysed by real-time polymerase chain reaction (RT-PCR), and protein expression levels of PI3K and Akt were detected by Western blot. A nitrite assay was used to measure intracellular nitric oxide (NO) production, and nitric oxide synthase (NOS) was measured by the T-NOS colorimetric method. Results: Animal experiments demonstrated that BHT significantly restored ET-1 and NO in animal peripheral blood, which were disordered in LPS-induced fever rabbits. Moreover, a cytotoxicity assay demonstrated that BHT ≤700 μg/mL is innoxious to RVECs. BHT significantly repressed cellular TNF-α, IL-1β, and ET-1, which were originally elevated by LPS in RVECs. Meanwhile, BHT elevated the gene expression level of the ETB receptor and promoted NOS and NO production in RVECs induced by LPS. Conclusion: BHT can inhibit excessive ET-1 secretion induced by LPS in vascular endothelial cells and activate the classic ET-1 signalling pathway to promote NO production, which may facilitate vasodilation of smooth muscle cells. Graphical abstract: Image 1 Highlights: Bai-Hu-Tang inhibits LPS inflammatory response in vascualar endothelial cells. Bai-Hu-Tang inhibits excessive secretion of endthelin-1 induced by LPS in vascualar endothelial cells. Bai-Hu-Tang activates classical ET-1 signaling pathway to promote NO production in vascualar endothelial cells.